Efficacy and safety of Ergoferon versus oseltamivir in adult outpatients with seasonal influenza virus infection: a multicenter, open-label, randomized trial. (October 2016) - Rafalsky, Vladimir; Averyanov, Alexander; Bart, Boris; Minina, Elena; Putilovskiy, Mikhail; Andrianova, Elena; Epstein, Oleg
Highlights: Ergoferon is similar to oseltamivir in terms of efficacy. Ergoferon improves quality of life. There are no serious adverse effects related to Ergoferon intake. Summary: Objectives: Ergoferon is an antiviral complex drug containing released-active forms of antibodies to interferon gamma, CD4, and histamine. Its efficacy and safety in the treatment of acute respiratory viral infections has been reported previously. The aim of this study was to compare Ergoferon with oseltamivir. Methods: A multicenter, open-label, randomized controlled trial of patients aged 18 to 65 years, who had tested positive for influenza A or B antigens, was performed. A total of 156 patients were enrolled as the intention-to-treat population; these patients were assigned randomly to receive either Ergoferon or oseltamivir ( n  = 78 in each group). Results: The percentage of patients achieving a normal body temperature (≤37.0°С) following 5 days of treatment did not differ significantly between the groups. The mean duration of fever in the Ergoferon and oseltamivir groups was 2.1 ± 1.5 days and 2.3 ± 1.6 days, respectively ( p  = 0.01). The average time to the resolution of influenza symptoms was approximately 3 days, with no significant between-group difference. Total quality of life scores were similar in the two groups following 5 days of drug administration. The incidence of adverse events did not differ significantly between the groups, nor were there any serious adverse events. Conclusions: Ergoferon and oseltamivir were equally effective and safe in adult outpatients with seasonal influenza A or B virus infection. Clinical trial registration: ClinicalTrials.gov identifier NCT01804946